Implementation of Public Information Disclosure in Creating Good Governance at Universitas Andalas - Azmaineti Fadila; Roni Ekha Putera; Ria Ariany (Universitas Teuku Umar, 2022)
Implementation of Public Information Disclosure in Creating Good Governance at Andalas University. In line with the demands for reform, good governance comes in the form of a new transplant which is expected to be able to take care of the bureaucracy which has been represented as a bureaucracy full of acts of corruption and abuse of power. Transparency is an important aspect of governance that demands an increasingly open and transparent government system. The enactment of the Information Disclosure Act is one aspect to increase public oversight of the government system. Writing this journal is intended to be able to provide an overview by analyzing the implementation of public information disclosure in realizing good governance at Andalas University as a government institution that is to provide the information needed in the implementation of higher education. This study uses descriptive qualitative methods, while for data collection techniques in this research study the authors conducted interviews, and documentation. The results of the study indicate that the implementation of Public Information Disclosure in Creating Good Governance at Andalas University is still not running optimally, this is caused by communication that does not go well, inadequate resources.